Life cycle assessment of culture media with alternative compositions for cultured meat production - Wali, Mohammad El; Karinen, Heini; Rønning, Sissel Beate; Skrivergaard, Stig; Dorca-Preda, Teodora; Rasmussen, Martin Krøyer; Young, Jette Feveile; Therkildsen, Margrethe; Mogensen, Lisbeth; Ryynänen, Toni; Tuomisto, Hanna L. (Springer Nature, 2024)
Purpose: Cultured meat is produced by cultivating animal cells in a bioreactor in a culture medium that provides nutrients and growth factors. Among other animal sera, fetal bovine serum (FBS) has traditionally been the most common used in the culture medium of mammalian cell cultures, i.e., 10% FBS medium that contains 10% FBS and 90% DMEM/F12 (v/v). As the aim of cultured meat is to replace livestock production, animal component-free culture media needs to be developed. Methods: We analyzed the environmental impact of replacing the 10% FBS culture medium with serum substitutes, i.e., growth factors, Essential 8™, protein hydrolysates from egg-white, eggshell membrane, poultry residues, pork plasma, and pea concentrate, and Tri-basal 2.0 + ITS medium that contains fibroblast growth factor (FGF-2), fetuin, bovine serum albumin (BSA), and insulin transferrin selenium (ITS). Life cycle assessment with a cradle-to-gate approach was used to quantify global warming potential, freshwater and marine eutrophication, terrestrial acidification, land use, water consumption, fossil resource scarcity, particulate matter formation, cumulative energy demand, and ozone formation of preparing 1-L culture medium. Sensitivity analysis was conducted to examine the impact changes under various production conditions including variations in the impact allocation strategy, production location, and energy sourcing. Results and discussion: The 2% FBS medium (2% FBS, 96% DMEM/F12, and 2% growth factors (v/v)) reduced all environmental impacts where marine eutrophication had the highest reduction (77%), while land use was the least affected with a reduction of 6%. The Tri-basal 2.0 + ITS and protein hydrolysates media reduced most of the analyzed environmental impacts. Protein hydrolysates from egg-white had the lowest environmental impacts reducing 81% global warming potential, 28% water consumption, 59% fossil scarcity, 87% eutrophying emissions, 91% terrestrial acidification, 82% particulate matter, and 70% ozone formation, compared to FBS-containing medium. Land use and energy demand were reduced the most by 17 and 37%, respectively, when the 10% FBS medium was replaced with the Tri-basal 2.0 + ITS medium. Conclusions: Changing the input of FBS in culture media from 10 to 2% (v/v) reduced all studied environmental impacts. Further reductions were achieved when FBS was totally replaced by basal media DMEM/F12, Essential 8™, protein hydrolysates, and recombinant growth factors. Land use was the least reduced, as it was driven by starch extraction to produce glucose for the DMEM/F12 basal medium. Culture medium with protein hydrolysates from egg-white achieved the highest impact reductions compared with the FBS-containing medium.
Keywords: serum-free; protein hydrolysates; cultured meat; life cycle assessment; environment; cellular agriculture